Effect of infusion of a triacylglycerol emulsion on low-density lipoprotein composition and oxidizability. - Callow, J; Samra, J; Frayn, K (1998)
Six, healthy, male volunteers aged 19-48 years received a 4-h infusion of a triacylgycerol emulsion (Intralipid 10%) after an overnight fast. Plasma triacylglycerol (TAG) and low-density lipoprotein (LDL) -TAG, -protein and -phospholipid concentrations all rose significantly during the course of the infusion and remained elevated 90 min after its end. The weight/weight ratio of LDL-TAG to -protein also increased significantly (from 0.43+/-0.14 to 0.79+/-0.30 at 4 h and 0.63+/-0.31 90 min later), indicating TAG-enrichment of LDL particles. There were no significant changes in LDL particle density. Susceptibility of LDL to copper-induced oxidation, as measured by the lag time for conjugated diene formation, was less at the end of and 90 min after the end of the infusion than in the fasting state (59.3+/-16.5, 47.4+/-17.4 and 34.8+/-19.6 min, respectively). Lag time was positively correlated with LDL TAG in the fasting state (rS=0.900, P < 0.0001) and the correlation continued with the post-infusion TAG-enriched LDL (rs=0.886, P < 0.05). Acute hypertriglyceridaemia induced by infusion of Intralipid therefore causes TAG-enrichment and a decrease in the susceptibility to oxidation of LDL. TAG-enrichment of LDL may lead to subsequent potentially atherogenic changes in LDL following TAG hydrolysis.